ACOUSTIC EMISSION AND THE PRECURSORY PHASES OF FAILURE IN A LABORATORY EXPERIMENT - Sobolev G.A.; Ponomarev A.V. (My University, 2000)
The space-time distribution of hypocenters emitting acoustic signals in a range of energy was investigated during a specially prolonged formative period of macrofailure in a granite specimen under a triaxial compression. Failure nucleation was accompanied by a sudden increase in acoustic emission rate and a decrease in the external load, the relative frequency of lower energy signals decreasing and that of higher energy signals increasing. This phenomenon occurred before the decrease of external load, thus forecasting it. Two different distributions of acoustic signals were recorded, within the incipient rupture and outside it. The relative frequency of acoustic signals of lower energies decreased within the rupture volume, and simultaneously increased in the outer zone. The signals of higher energies behaved in an opposite manner. Rupture occurred during a transition from smaller to larger failure. The rupture process involved an acoustic quiescence during which signals of lower energies became relatively more frequent again. Chains of clusters consisting of acoustic signals with different energy classes were studied. They preceded both the generation of the rupture volume as a whole and the occurrence of individual large acoustic events within this volume. This approach can be used to identify the deterministic part of acoustic activity and derive a better predictable model of the process. The spatial distribution of clusters of epicenters indicates the area of the future macrofailure. It is presumed that these features of acoustic activity and its phases revealed in this laboratory experiment can be used to monitor the evolution of real earthquake ruptures.